Clinical characteristic, psychometric properties, novel diagnostic methods and outcomes in interstitial lung diseases - Krauss, Ekaterina; Justus Liebig University Giessen (My University, 2022)
In this research, we report detailed clinical characteristics of a large European IPF cohort with outcome data extending up to 10 years. Our patients are diverse in age, impairment of lung function, therapeutic regimes and co-morbidities. In this regard, the diversity of the eurIPFreg- cohort may reflect not only the variety in natural course of the disease, but also changes in clinical management of the patients, especially when comparing our results to historic IPF data and data from controlled clinical phase III trials. Thus, the decline in the usage of prednisolone and other immunosuppressive medication reflects the implementation of recent IPF guidelines, and the knowledge arising from the PANTHER-IPF trial, according to which these therapeutic strategies are rather harmful than helpful in IPF. Our registry data also reflect the steady increase in the use of cryobiopsy for diagnosis and of usage of antifibrotic drugs. However, our data indicate that IPF still has a high mortality rate and that survival times are quite heterogenous, reflecting both, the heterogeneous natural course of IPF in a clinical setting, ranging from stable disease to a rapid progressive fibrosis, and the change in the pharmacological approach to IPF subjects. The presented work also reflect changes in the diagnostic and therapeutic approach in IPF in the last ten years, supporting the important role of large real-world data registries to document and scrutinize changes in IPF management. Furthermore, a real-life ILD-data registry significantly complements data from randomised controlled trials, typically comprising a wide range of severity, progression and co-morbidities. Prognostic indicators for IPF patients under antifibrotic treatment have yet to be established in the future, using epidemiological data and taking into account a larger numbers of patients with definite outcome data and longer follow up periods.
Klinische Charakteristik, psychosoziale Merkmale, neue Diagnostikmethoden sowie Überlebensanalysen bei interstitiellen Lungenerkrankungen
Keywords: Interstitielle Lungenerkrankungen; Idiopathische pulmonale Fibrose; eurIPFreg; eurILDreg; ddc:610